Current practice in management of pelvic girdle pain amongst physiotherapists in Norway and Australia - Beales, Darren; Hope, J.; Hoff, T.; Sandvik, H.; Wergeland, O.; Fary, Robyn (Churchill Livingstone, 2014)
Pelvic girdle pain (PGP) is frequently managed by physiotherapists. Little is known about current physiotherapy practice and beliefs in the management of PGP disorders. The primary aim of this study was to investigate current practice and beliefs in management of PGP among physiotherapists working in Norway and Australia. A secondary aim was to compare current practice with clinical guidelines. A questionnaire was developed and electronically distributed to physiotherapists in Norway (n = 65) and Australia (n = 77). Treatment and management were determined via responses to 2 case vignettes (during pregnancy, not related to pregnancy), with participants selecting their four primary preferences for treatment and management from a list of 33 possibilities. During pregnancy, ‘education around instability’ and ‘soft tissue treatment’ was selected amongst the most common interventions by physiotherapists in both countries. Norwegian physiotherapists selected ‘pelvic floor exercises’ more frequently, while Australian physiotherapists more commonly selected ‘correcting functional impairments’. In the other case, common responses from both countries were ‘hip strengthening in weight bearing’ and ‘correction of functional impairments’. Norwegian physiotherapists selected ‘general physical exercise’ and ‘general education’ more frequently, while Australian physiotherapists more commonly selected ‘hip strengthening in non-weight bearing’ and ‘muscular relaxation of the abdominal wall/pelvic floor’. Beliefs about PGP were generally positive in both groups while knowledge of and adherences to clinical guidelines were limited. The findings provide direction for future research related to the management and treatment of PGP, and targets for education of physiotherapists working in this area.